Inhibition of CX3CL1 by treadmill training prevents osteoclast-induced fibrocartilage complex resorption during TBI healing - Liu, Xiao; Zhou, Mei; Tan, Jindong; Ma, Lin; Tang, Hong; He, Gang; Tao, Xu; Guo, Lin; Kang, Xia; Tang, Kanglai; Bian, Xuting (Frontiers in Immunology, 2024)
The healing of tendon-bone injuries is very difficult, often resulting in poor biomechanical performance and unsatisfactory functional recovery due to inflammation, scars, and other reasons. The tendon-bone insertion has a complex four distinct layers structure, and previous studies have often focused on promoting the regeneration of the fibrocartilage layer, neglecting the role of its bone end repair in tendon-bone healing. Based on the discovery that treadmill training can inhibit osteolysis and promote tendon-bone healing, this study identifies the cytokine CX3CL1 that was significantly inhibited locally at the tendon-bone insertion after treadmill training. Next, we used CX3CL1 recombinant protein and its receptor (CX3CR1) antagonist protein AZD8797, respectively, to prove that CX3CL1 can promote the differentiation and formation of osteoclast in vitro, while AZD8797 can inhibit the formation of osteoclast in vivo and in vitro, improve tendon-bone healing, and improve the biomechanical properties and motor function of tendon-bone insertion after healing. In conclusion, we proved that treadmill training can inhibit the formation of osteoclast, reduce osteolysis and ultimately improve tendon-bone healing by inhibiting the secretion of CX3CL1 at the tendon-bone insertion.